Peran Media Sosial Untuk Pengembangan Brand Awarness dan Pemasaran Produk Disabelitas (DISKRAF) Pada Kelompok Binaan PT.Langgeng Makmur Wijaya: Mitra PKM: PT. Langgeng Makmur Wijaya - Erza Sofian; Asri Pertiwi; Risman Nugrahan; Syiffa Rie Siregar; Annisa Nur Fadilah; Kynta Putri Syakira; Muammar Ar Rizki; Sarah Muthia Rahma Anggraini; Shafa Khairunnisa Azzahra (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Refers to the Government of the Republic of Indonesia Regulation No. 7 of 2021 on the facilitation, protection, and empowerment of cooperatives and micro, small, and medium-sized enterprises. With this we from the team of lecturers of the Information Systems study program to implement from the government regulation of the Republic of Indonesia No.7 of 2021, for the preparation of business development strategies of SMEs in the utilization of technology. Utilizing digital technology to introduce its products and services to the public at large, especially among people with disabilities (Diskraf). This can be done either through online chat applications (Whatsapp, LINE, telegram, etc.), social media (Facebook, Instagram, Twitter, etc.), online stores on various e-commerce platforms (Bukalapak, Tokopedia, Blibli, etc.), own websites, to the use of various applications or other business support software. ESQ Business School (STIMIK ESQ), with the University's tri dharma program namely Community Service, ESQ College of Management Science and Computer Science, the Information Systems study program provides coaching, strategy workshops, and information technology for the management of a business/business. This strategy direction can be used in the future by MSME managers/participants in carrying out their business or business processes. Therefore, if a business process performs the strategy and mastery of the Information System well, then the business will be successful in carrying out their business or business in the future.